The Impact of Urbanization on Bird Population and Its Status in Muzaffarpur, Bihar, India (International Journal of Scientific Research in Science and Technology, 2025)
Urbanization is a major driver of biodiversity loss and ecological change globally, with pronounced effects on avian communities. As urban centers expand, natural habitats are replaced by modified human-made systems, leading to shifts in bird species composition, richness, and abundance. This paper reviews the general impacts of urbanization on bird populations, analyzes the specific context of rapid urban growth in Muzaffarpur, Bihar, and synthesizes available data to propose a status report and areas for future research. While some generalist and exploiter species thrive in urban environments, many specialist and native bird species, particularly those with specific foraging or nesting requirements, are on the decline. The proliferation of pollutants, noise, artificial light, habitat fragmentation, and predation from domestic animals pose significant threats to avian diversity in the city. The findings emphasize the need for conservation-focused urban planning in Muzaffarpur to preserve and restore avian biodiversity.